Ulee's gold [videorecording (DVD)] - Nunez, Victor; Nunez, Victor; Fonda, Peter, 1940-2019; Richardson, Patricia, 1951-; Biel, Jessica, 1982- (MGM limited edition collection., 1997)
Captures the essence of a man who escapes one war only to find himself at battle with his wounded spirit. He methodically tends his bees, carefully provides for those that need him and vigilantly keeps his emotions at bay, buts finds that he must break through his emotional walls when everything is threatened by a long-buried secret.